Aptamer as a Targeted Drug Delivery - Devsing, Sadar Mayur; Sarode, Rahul; Khandelwal, Saloni; Biyani, Kailash R (Asian Journal of Pharmaceutical Research and Development, 2020)
Aptamers are the synthetic oligonucleotides which are short single-stranded in nature with having three-dimensional shape or structure. From the past few years, Aptamers as inventive targeting molecules play an important role in the biomedical field. Aptamers are generated by the method termed as SELEX. Aptamers have a unique feature in which they bind to the desired targets or the receptors on the cell membrane utilizing their high affinity and specificity. So, for drug delivery as targeting ligands, aptamers can be provided. In the research field, for monitoring the environment and ensure the food safety aptamers are generally used. They also used as a therapeutic agent and plays an important role in clinical diagnosis. An Aptamer is a fascinating tool that is mainly used in molecular biology applications, as well as potential pharmaceutical agents and the reason behind this fascinating tool, is the various unique properties of the aptamer. Aptamers have more advantages over antibodies. They can be selected against bacteria and viruses. This review provides an overview of the development of Cell-Specific aptamers for targeted drugs along with the advantages, uses, and applications of aptamers.